The influence vaginal irrigations of postoperative period at the patients after vaginal operations - Malinowski, Andrzej; Mołas, Justyna; Maciołek-Blewniewska, Grażyna (Menopause Review/Przegląd Menopauzalny, 2006)
Objectives: The aim of this work is the retrospective comparison of postoperative period after vaginal operations during witch were applied only vaginal knobs including metronidazol or except for vaginal knobs irrigations with a solution containing of Benzydamine was applied. Materials and methods: Patients were divided in two groups. The group A – 246 patients of whom only vaginal knobs were applied of postoperative period. The group B – 666 patients of whom also vaginal irrigations were applied. In both studied groups of patients in postoperative period after 4, 6, 8 and 12 weeks the healing of the vaginal wound were estimated. Results: The time of healing vaginal wound is statistically shorter in group B in comparison to group A. The granulation was formed more rarely in group B and the same was with the infections of the wound. Conclusions: Vaginal irrigations with a solution of Benzydamine influence positive on healing the wound in vaginal surgery.